Biomechanical effects of menopause in ovariectomized rats' femurs - Okyay, Ayse Guler; Kavak, Servet; Turktas, Ugur; Alkis, Ismet; Guner, Savas; Aksakal, Bunyamin (Informa Healthcare, 2014)
Objective: To demonstrate the biomechanical changes in rat bones occurred by surgical menopause and to search for correlation between biomechanical test results and bone mineral density (BMD) measurements. Methods: Thirty female Wistar-albino rats aged 6 months and weighed 250-300 g were randomized into ovariectomy, sham and control groups. After 6 months, rats were sacrificed and right femurs were extracted. BMD measurements and three point bending biomechanical tests were made in femurs. Results: The difference among the mean BMD measurements of three groups were found to be statistically significant (Pr>F value <0.0001). Mean elastic module, maximum elongation and femoral diameters were also found to be statistically significantly different (Pr>F value <0.05). Ovariectomised and sham-operated groups were significantly different in terms of elastic modulus. Ultimate force did not differ among the groups significantly. The difference between ultimate strain and maximum elongation of the ovariectomy and sham operated group was statistically significant. Conclusions: Bone quality was deteriorated and fragility was increased in rats 6 months after surgical menopause. Sole BMD measurement might not be reliable in evaluation of osteoporosis and fracture risk. Biomechanical quality of bone is more important than its mineral content in determining fragility.
Keywords: Biomechanics; menopause; osteoporosis; ovariectomy; rat